Remediation - Remediation (Wiley, 2026)
Remediation is an environmental management journal publishing research on environmental clean-up techniques, technologies and costs needed in the world today. Articles focus on the practical applications of remediation techniques and technologies.
FI 0.26
Q3
Keywords: Earth; Space & Environmental Sciences; Environmental Management; Policy & Planning; Gestión; Política y Planeamiento ambiental; Acuerdos transformativos; Transformative agreements; Residuos peligrosos; Biorremediación; Residuos tóxicos